Chemically Treated Bamboo With Sodium Hydroxide And Potassium Hydroxide - Goh, Zi Qi (Universiti Sains Malaysia, 2022)
The usage of bamboo in the building sector is not a recent development. Due to its strength, durability, and capacity to substitute steel in concrete, bamboo is a natural resource with a large population and potential for usage in building. However, the high starch content of bamboo makes it particularly susceptible to the effects of the elements when sap or humidity levels are high. Harvested bamboo may be quickly harmed by insects, fungi, rot, and fire if it is not chopped, handled, and stored properly. Thus, this study evaluated how alkaline treatment affected the mechanical and physical features of local bamboo. The objective is to treat bamboo Gigantochloa Ligulata and bamboo Gigantochloa Scortechinii with alkali and determine its characteristic as a sustainable resource for building construction. Additionally, the effects of chemical treatment with NaOH and KOH applied to bamboo intended for use as a construction material were investigated. NaOH solution and KOH solution were used to discover the best alkali for treating bamboo. After being submerged in the alkali solution for 24 hours, the bamboo was dried. Both treated and untreated bamboo were examined using Fourier Transform Infrared Spectroscopy (FTIR), and the moisture content was measured using a moisture meter. Besides, the mechanical properties of the bamboo was determined using tensile testing machine and also compression machine. According to the research, treated bamboo may be a practical replacement for wood in the construction of buildings, better to those natural bamboo in terms of resistance. The bamboo treated with sodium hydroxide (NaOH) show the highest strength in compression and tensile strength which make it suitable to use as building material.